Proustian Metaphor and the Automobile - Shawn Gorman (Studies in 20th & 21st Century Literature, 2005)
In Marcel Proust's Sodome et Gomorrhe, the automobile produces a transformation in the relationship between space and time and, by analogy, a parallel transformation in art. In Proust's famous notion of involuntary memory, the similarity of a past sense impression to a present one leads to transcendence of time and space, and ultimately to metaphor. The metonymical speed of the automobile endlessly chases the sort of metaphorical "simultaneity" at work in involuntary memory. Structurally, the automobile offers the possibility of bringing together two terms by eliminating the middle term (time, space) that separated them; yet the automobile is never fast enough to reach the atemporal perfection of metaphor, and the third term reappears. We therefore examine how the automobile in this and other texts by Proust exhibits both metaphorical and metonymical properties. The automobile creates unexpected connections and reveals, in a displaced form, surprising relationships among characters, emotions, objects, and symbols. In its role as metaphor, the automobile stands for processes that are negatively marked, like aesthetic fetishism, while in its role as metonymy, the automobile leads to pleasure and appeasement.
Keywords: Marcel Proust; Sodome et Gomorrhe; automobile; space; time; space and time; art; involuntary memory; simultaneity; metaphor; characters; emotions; objects; symbols; fetishism; pleasure; metonymy